Effect of Entrepreneurial Activities in Internationalization on Firm Performance: Balfour Beatty PLC - Charoenvisal, Mingmit (2012)
International Entrepreneurship has gained a lot of attention from researchers and practitioners over the last few years. This is mainly due to the impact of entrepreneurship and internationalisation on global business. The purpose of this research is to study the effects of two concepts when combined together. The scope of the research has been drawn to answer the question ‘Do entrepreneurial activities in internationalisation affect company performance?’ and specifically tailored for Balfour Beatty PLC. The result confirms the findings of former literature that entrepreneurship presents the positive relationship to the firm performance. The entrepreneurial aspect applied in this research consists of innovation, risk-taking and proactiveness. With reference to firm performance, Balfour Beatty displays innovation through internationalisation by developing new integrated services, manages risk to avoid unexpected circumstances and is proactive in improving core capabilities and gauges environmental hostility frequently. All this pushes them to achieve a great performance. The benefits of this research could be increased further by expanding the scope to other entities, especially within the same industry with a longer period of study to better gain an explicit result. Additionally, the academic study could be improved by researching the effect of entrepreneurship on sustainability. And to study how entrepreneurship contributes benefits to all engaged stakeholders in the long term rather than just the company.